2023
DOI: 10.1155/2023/6726654
|View full text |Cite
|
Sign up to set email alerts
|

JFD, a Novel Natural Inhibitor of Keap1 Alkylation, Suppresses Intracellular Mycobacterium Tuberculosis Growth through Keap1/Nrf2/SOD2-Mediated ROS Accumulation

Abstract: It is an effective strategy to treat tuberculosis by enhancing reactive oxygen species- (ROS-) mediated killing of Mycobacterium tuberculosis in macrophages, but there are no current therapeutic agents targeting this pathway. Honeysuckle has been used as the traditional medicine for tuberculosis treatment for 1500 years. Japoflavone D (JFD) is a novel biflavonoid isolated from Honeysuckle promoting ROS accumulation by Nrf2 pathway in hepatocarcinoma cells. However, its activity to kill M. tuberculosis in macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Only few studies investigated the role of NRF2 in mycobacteria infection [ 78 ]. In Mtb-infected macrophages, it has been shown that activation of NRF2 is associated with enhanced bacterial load and cell survival [ 79 ], while inhibition of NRF2 or NQO1 ensured a better control of Mtb or BCG infection and host cell survival [ 80 , 81 ], suggesting that NRF2-NQO1 axis, by detoxifying ROS, might play a detrimental role during mycobacteria infection. By contrast, Zhou et al showed that the activation of NRF2-NQO1 axis induced better control of Mtb [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only few studies investigated the role of NRF2 in mycobacteria infection [ 78 ]. In Mtb-infected macrophages, it has been shown that activation of NRF2 is associated with enhanced bacterial load and cell survival [ 79 ], while inhibition of NRF2 or NQO1 ensured a better control of Mtb or BCG infection and host cell survival [ 80 , 81 ], suggesting that NRF2-NQO1 axis, by detoxifying ROS, might play a detrimental role during mycobacteria infection. By contrast, Zhou et al showed that the activation of NRF2-NQO1 axis induced better control of Mtb [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…These investigations establish a solid theoretical foundation for the therapeutic and interventional approaches targeting Keap1 PTMs in oxidative stress-related ailments. Notably, numerous naturally occurring compounds derived from plants, such as genistein ( Tocmo and Parkin, 2019 ), Japoflavone D ( Wan et al, 2023 ), and luteolin ( Nakamura et al, 2018 ), have been experimentally validated to exhibit favorable effects on diseases through the activation of the Nrf2 pathway in both cellular and animal models. However, it should be noted that these substances do not directly alter or engage with Nrf2.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, they indirectly impact Nrf2 by regulating the PTMs of Keap1. Consequently, they hold potential for the treatment of oxidative stress-related ailments like diabetic heart (I/R) injury ( Nakamura et al, 2018 ), tuberculosis ( Wan et al, 2023 ), and cerebral ischemia cognitive decline ( Tocmo and Parkin, 2019 ) ( Figure 2 ). This suggests that Keap1 could be a promising therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genes GPX3, SOD2 , and CAT of the above three enzymes were verified by RT-qPCR, and it was found that the expression of GPX3 and SOD2 increased after infection, whereas the expression of CAT decreased. Many studies ( Ren et al., 2021 ; Wan et al., 2023 ) have shown that SOD2 is upregulated and regulates ROS in macrophages infected with MTB, but there are few reports of GPX3 and CAT . Among them, the high expression of GPX3 and SOD2 may be an adaptive change of macrophages in response to OS caused by MTB, to reduce ROS levels, maintain the normal function of macrophages, and prevent death.…”
Section: Discussionmentioning
confidence: 99%